Selection and Validation of Reference Genes for Quantitative Real-Time PCR Normalization in Athetis dissimilis (Lepidoptera: Noctuidae) Under Different Conditions - Tang, Jinrong; Liang, Gemei; Dong, Shaoqi; Shan, Shuang; Zhao, Man; Guo, Xianru (Frontiers in Physiology, 2022)
Quantitative real-time PCR is an important tool for studying gene expression patterns using reliable reference genes. Athetis dissimilis is an important agricultural pest, but to date, no studies on the stability of its reference genes have been reported. Here, 10 candidate genes (18S, 28S, AK, EF1-α, GAPDH, RPL32, RPL40, α-TUB, β-ACT and β-TUB) of A. dissimilis were selected and evaluated as suitable reference genes stably expressed under different biotic and abiotic conditions. The stability of their expression levels was analyzed using five tools, geNorm, NormFinder, BestKeeper, Ct and RefFinder. Furthermore, the target genes CSP1 and SOD were used to validate the reference gene selection. The most stable candidate reference genes were as follows: EF-1α, RPL40 and 18S for developmental stages, RPL40 and α-TUB for larval tissues, α-TUB and 28S for adult tissues, EF-1α and β-ACT for insecticidal treatments, β-ACT and 28S for temperature treatments, EF-1α and β-ACT for starvation treatments, RPL40 and 18S for dietary treatments, and 18S, 28S and α-TUB for all the samples. This report provides suitable reference genes for studying gene expression in A. dissimilis under different experimental conditions, and it also provides a reliable foundation for further gene functional studies in A. dissimilis.